Resposta do feijoeiro à aplicação de N, P, K e calcário na Zona da Mata, Minas Gerais - Nogueira Fontes, Luiz Antônio; Ribeiro Gomes, Fábio; Vieira, Clibas (Revista Ceres, 2025)
Fertility experiments to study the yield response of beans (Phaseolus vulgarisL.) to N, P, K, and lime were established on locations at Ponte Nova (two experiments), Ervãlia, Inhapim, Viçosa and Ubá in the State of Minas Gerais. The fertilizers used as sources of the above elements were ammonium sulfate, ordinary superphosphate, and potassium chloride. The limestone used was calcitic. All were applied at planting time.